ANTI-INFLAMMATORY AND ANTIOXIDANT ACTIVITIES OF PHENAX rugosus (POIR.) WEDD AND TABEBUIA chrysanta G. NICHOLSON. - Luis Fernando OSPINA Giraldo (Universidad de Antioquia, 2011)
The inflammation is a multifactorial and highly regulated process associated to several chronic and degenerative diseases. Due to a lot of inflammatory process are sometimes characterized by oxidative stress, it has been demonstrated that antioxidants are useful as anti-inflammatory agents. The species Phenax rugosus (Poir.) Wedd and Tabebuia chrysanta G. Nicholson are used in the “Eje Cafetero” of Colombia by their antiinfeccious and immunomodulatory properties. In this work we evaluate in vivo anti-inflammatory and in vitro antioxidant properties of these plant species. We use two acute inflammation models: TPA-induced mouse ear oedema and carrageenan-induced rat paw oedema. In vitro antioxidant activity is evaluated against hydroxyl, peroxyl and superoxide radicals. The aquose extract of Phenax rugosus is promising because of their anti-inflammatory and antioxidant activities. These results are a rational for ethnopharmacological use of these plant species.